Olfactory marker protein gene: its structure and olfactory neuron-specific expression in transgenic mice. - Danciger, E (1989)
Olfactory marker protein (OMP) genomic clones were isolated from a Charon 4A phage lambda rat genomic library. A 16.5-kilobase (kb) fragment of the rat genome containing the gene was isolated and characterized. Sequence analysis of the gene showed the absence of introns and the lack of CAAT and TATA boxes in the 5' flanking region. The transcription initiation site was mapped, and two sites 55 and 58 base pairs upstream of the ATG were observed. The 5' flanking region is rich in G+C residues and contains a G+C-rich motif as well as direct and inverted repeats. Functional OMP regulatory sequences were demonstrated in transgenic mice. An 11-kb chimeric gene was constructed in which the coding region for OMP was replaced with that for Thy-1.1. In Thy-1.2 mice carrying this transgene, Thy-1.1 was expressed solely by olfactory receptor neurons and their axons and terminals in the olfactory bulb.